(untitled) (International Conference on Education, Psychology and Humanities, 2026)
Multilingual United Nations documentation represents a complex institutional environment in which specialized concepts are expressed through different linguistic systems while being expected to preserve a high degree of semantic and terminological consistency. The present study examines the relationship between semantic variation and terminological convergence in multilingual United Nations documents. The central problem addressed in the study concerns the coexistence of linguistic variation and institutional standardization: equivalent concepts may receive structurally, semantically or contextually different realizations across languages, while institutional communication simultaneously requires stable and recognizable terminology. The research adopts a corpus-based comparative approach and analyses multilingual terminological correspondences in official United Nations documentation.